Association of MIR137 With Symptom Severity and Cognitive Functioning in Belarusian Schizophrenia Patients - Kandratsenka, Hanna; Nestsiarovich, Anastasiya; Goloenko, Inna; Danilenko, Nina; Makarevich, Anna; Obyedkov, Victor; Davydenko, Oleg; Waszkiewicz, Napoleon (Frontiers in Psychiatry, 2018)
MicroRNA-137 (miRNA-137; miR-137) is one of the important post-transcriptional regulators of the nervous system development, and its MIR137 gene rs1625579 polymorphism was reported to be a potential regulator for schizophrenia susceptibility. However, schizophrenia characteristics controlled by MIR137 rs1625579 polymorphism are still insufficiently understood. There were 3 groups included in the study: a) subjects with diagnosis of schizophrenia (n=150; 81-females, 69-males), b) mentally healthy people (control group; n=102; 66-females, 36-males) and c) Belarusian indigenous male group (n=295). Associations of rs1625579 with schizophrenia, symptom’s severity and cognitive performance (by using Positive and Negative Syndrome Scale –PANSS and Wisconsin Card Sorting Test -WCST, respectively) were studied, when compared to controls. Allele and genotype frequencies were investigated in Belarusian indigenous males. Rs1625579 displayed no association with schizophrenia in Belarusian population. Significant „symptom severity-genotype” interactions were revealed for schizophrenia patients. Patients with T/G genotype displayed lower severity of positive symptoms and general psychopathology compared to homozygous subjects. T/T genotype was associated with the highest symptom’s severity. The negative symptom scores and the total PANSS-score were significantly higher in females carrying genotype T/T vs. T/G+G/G; no significant gene-phenotype associations were found in males. WCST parameters did not show any association with rs1625579 polymorphism. MIR137 rs1625579 polymorphism might be an important sex-dependent factor influencing severity of schizophrenia psychopathological manifestations. These findings also contribute to the knowledge on candidate gene effects on characteristics related to schizophrenia phenotype. As miR 137 is considered to be cancer therapeutic target, miR-137 may also explain the lower incidence of cancer in schizophrenia patients. Further studies with larger sample size are needed to confirm these novel findings.